Cobalt, iron co-incorporated Ni(OH)2 multiphase for superior multifunctional electrocatalytic oxidation. Issue 100 (2nd December 2021) - Hao, Pin; Xu, Ruirui; Wang, Qian; Zhao, Zhenhuan; Wen, Houguang; Xie, Junfeng; Lei, Fengcai; Cui, Guanwei; Tang, Bo
Abstract : The Co, Fe co-incorporated Ni(OH)2 multiphase displays superior activity for electrocatalytic oxidation, benefitting from the multiphase and polymetallic synergy, as well as the perfectly exposed active sites. Abstract : The cobalt, iron co-incorporated Ni(OH)2 multiphase displays superior catalytic activity and stability for multifunctional electrocatalytic oxidation, ascribed to the multiphase synergy, enhanced charge transfer and well-exposed active sites.